Spontaneous melanotic lesions in axillary seabream, Pagellus acarne (Risso) - Ramos, Paula (2013)
In this paper, we describe spontaneous melanotic lesions in the skin of axillary seabream, Pagellus acarne (Risso) from a defined area of the Portuguese Coast, located in Cabo da Roca and Foz do Arelho. The lesions corresponded to black pigmentation spots on the skin of the head, fins, lips and conjunctiva and, additionally, black nodules on the skin of the head and lips. In some specimens, the nodular formations in the head changed their anatomical conformation. Histologically, there were melanophores scattered along the basement membrane or forming aggregates in the dermis, infiltrating the subcutaneous tissue but not invading the adjacent muscle tissue. The aim of this study was to characterize the macroscopic and microscopic features of the pigmented lesions. These fish show sessile hyperpigmented lesions (spots) that correspond to proliferative lesions of melanophores in the dermis and nodular lesions that correspond to neoplastic lesions, melanophoromas. The melanophores in such lesions showed high concentration of melanin in the cytoplasm, moderate pleomorphism and compact distribution throughout all of the dermis.